John S. Bergsma and Jeffrey L. Morrow, Murmuring Against Moses: The Contentious History and Contested Future of Pentateuchal Studies (Steubenville, OH: Emmaus Academic, 2023) - Lemański, Janusz (Verbum Vitae, 2024)
Book review: John S. Bergsma and Jeffrey L. Morrow, Murmuring Against Moses : The Contentious History and Contested Future of Pentateuchal Studies (Steubenville, OH: Emmaus Academic, 2023). Pp. 308. 39,95 USD. ISBN: 978-1-64585-149-3 (hardcover), 978-1-64585-150-9 (paperback), 978-1-64585–151-6 (e-book).